POTENSI ABALON TROPIS Haliotis asinina L. SEBAGAI SUMBER INOKULUM JAMUR SIMBION PENGHASIL ANTIMIKROBA - Litaay, Magdalena; Sari, Karlina; Gobel, Risco B; Haedar, Nur (Hasanuddin University, 2017)
The research about “The Potencial of Tropical Abalone Haliotis asinina L. As Source of Mushroom Antimicroba ProducingSymbionts” had been done. This research aimed to know the abalone potency as a source of inoculum and to characterizeisolate fungal symbionts H. asinina L. Isolation of fungi symbionts H. asinina L. was performed used a PDA medium (PotatoDextrose Agar). Characterization of isolates fungal symbiont from H. asinina L. consists of macroscopic and microscopicobservations, and activity testing against pathogenic bacteria and fungi. The results showed that there were isolates of fungalsymbionts H. asinina L. (Abl.J.1, Abl.J.2, and Abl.J.3). The results of macroscopic observation colony indicated Abl.J.1 andAbl.J.3 isolate had a surface likes flour and Abl.J.2 isolate had a flat surface such as cotton; Abl.J.1 isolate green, Abl.J.2 isolatelight green and Abl.J.3 isolate black in colours. Three isolates had concentric circles; isolates Abl.J.1 and Abl.J.3 had radiallines and isolate Abl.J.2 had not radial line. The result of microscopic observation showed that three isolates had not septa,and hyaline (colorless); three isolates had asexual spores conidioshpore and all isolates was suspected to belong to the genusAspergillus. All isolates were able to inhibit the growth of Salmonella thypi bacteria and Candida albicans fungus and theresulting compounds were bacteriocidal and fungicidal.Keyword: Gastropods, H. asinina L., Symbiont fungus, Antimicrobal, Aspergillus.